2005
DOI: 10.1177/159101990501100303
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Complications Arising during Cerebral and Spinal Diagnostic Angiography from 1998 to 2003

Abstract: This retrospective study aimed to assess the percentage of complications in the daily practice of cerebral and spinal cord diagnostic angiography at our institution and to compare this with literature reports published in the last twenty years and guidelines for angiography. From 1st December 1998 to 1st December 2003 2154 patients underwent digital angiography for a total of 5996 vessels selected. Three neurological complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…The most feared complication is stroke, the incidence of which is <1% when the procedure is performed by experienced physicians. [118][119][120][121][122][123][124][125] Angiography may be the preferred method for evaluation when obesity, renal dysfunction, or indwelling ferromagnetic material renders CTA or MRA technically inadequate or impossible and is appropriate when noninvasive imaging produces conflicting results. In practice, however, catheter-based angiography is unnecessary for diagnostic evaluation of most patients with ECVD and is used increasingly as a therapeutic revascularization maneuver in conjunction with CAS.…”
Section: E90mentioning
confidence: 99%
“…The most feared complication is stroke, the incidence of which is <1% when the procedure is performed by experienced physicians. [118][119][120][121][122][123][124][125] Angiography may be the preferred method for evaluation when obesity, renal dysfunction, or indwelling ferromagnetic material renders CTA or MRA technically inadequate or impossible and is appropriate when noninvasive imaging produces conflicting results. In practice, however, catheter-based angiography is unnecessary for diagnostic evaluation of most patients with ECVD and is used increasingly as a therapeutic revascularization maneuver in conjunction with CAS.…”
Section: E90mentioning
confidence: 99%
“…Previous reports have indicated that incidental embolism is not rare, and past history of vasculopathy, amount of contrast medium used, fluoroscopy time, use of additional catheters, procedures of the occlusion test, and performance of endovascular surgery for cerebrovascular disease are risk factors for embolism. 1,4,5,8,9,11,13,16,17,20,21) Angiography of the coronary arteries also carries a risk for cerebral embolism due to the duration of the procedure. 4,15) Diffusion-weighted MR imaging (DWI) allows for the most sensitive early detection of cerebral ischemia within minutes of onset.…”
Section: Introductionmentioning
confidence: 99%
“…Digital subtraction angiography (DSA) is still considered the gold standard for the diagnosis of intracranial vascular pathologies, and these conditions are increasingly being treated through endovascular approaches. Although safety profiles for diagnostic and interventional neuroendovascular procedures in adults have been described, 2,4,5,11,12,14,16,23,24,30,[32][33][34]36,38 the complication rates for children during and after such procedures have not been well established. Children have unique anatomy and physiology, which renders cerebral angiography and intervention more challenging than analogous procedures in adults.…”
mentioning
confidence: 99%